Postpartum serum biochemical profile in Mehsana buffaloes during non-fertile and fertile oestrus - PATEL, K K; JACOB, NINAN; KAVANI, F S; VADODARIA, V P (The Indian Journal of Animal Sciences, 2013)
Eighteen normally calved Mehsana buffaloes studied for postpartum oestrus (non-fertile and fertile oestrus) revealed higher levels of serum total cholesterol (P<0.05) and serum inorgaic phosphorus, alkaline phosphatase and acetylcholinesterase enzymes during fertile oestrus as compared to non-fertile oestrus. However,a reverse trend was observed for serum calcium. The findings revealed that total cholesterol levels were more useful thatn other estimates.